Relationships Between Service Quality, Store Image, Customer Satisfaction, And Customer Loyalty - Anam, Chairul; Mujib, Abdul (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Over the last few years, MSMEs have become the main motor in driving economic growth. In today's increasingly fierce competitive conditions, business competitors continue to strive to provide high quality services, create an excellent brand image, with the aim of meeting customer satisfaction and maintaining their loyalty. The aim of this research is to empirically examine the relationship between service quality, store image, customer satisfaction, and customer loyalty. We collected research data on consumers who purchased MSME products at the Mojokerto City Center for Featured Products, using accidental sampling techniques. We propose a conceptual model from previous research and consider it in the context of superior MSME products in Mojokerto City. The analysis technique used is multiple linear regression analysis using the SPSS computer application program. The research results show that service quality and store image significantly impacts customer loyalty. Likewise, the research results also confirm that customer satisfaction significantly impacts customer loyalty at the Mojokerto City Center for Featured Products. In addition, the research results reveal that customer satisfaction strengthens the influence of store image on customer loyalty. This research suggests implications for managers, limitations and directions for future research of the above findings.